Analisis Afiks pada Fi`il Mujarrad dalam Surat Hud - Rohanda, Rohanda; Cahya Mahesa, Dzikri; Dayudin, Dayudin (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2025)
In an Arabic verb, there are several morphemes that form it. These morphemes are located at the beginning, middle, and end, which are usually called affixes. Affixes have an important role in a word, because the existence of these affixes can affect the meaning. One of the affixes that is often found in an Arabic verb is the affix located at the end (suffix), which functions to determine the subject, including in terms of distinguishing between masculine and feminine. This research aims to present some forms of affixes that exist in fi'il mujarrad in al-Qur'an surah Hud. The data of this research are Arabic words which are fi'il. This research belongs to descriptive qualitative research. The approach applied in this research is affixes on fi'il mujarrad viewed from the perspective of morphology. The data collection technique used is the documentation method with reading and recording techniques, and through two data analysis techniques, namely identification and analysis. The result of this research shows that in al-Qur'an surah Hud there are affixes on fi'il which are influential in (1) translation of fi'il mujarrad (2) formation of fi'il mujarrad (3) determination of subject or actor (4) distinguishing between masculine and feminine or determining gender (5) determination of quantity (6) determination of time (7) Indicators of command and prohibition sentences (8) Indicator of negation sentence . This research provides an overview of the influence of affixes on fi'il mujarrad, as well as providing a deeper understanding of the form and function of affixes in Arabic verbs